Employee Engagement Mediation: Employee Performance Through Employee Loyalty and Organizational Commitment - Milisani, Meirna; Devi, Nurwulan Kusuma; Naser, Haspul (GoAcademica Research & Publishing, 2024)
The automotive parts highly value the quality of production results, so it requires employee involvement to mediate employee loyalty and organizational commitment to improve employee performance. The quality demands of automotive parts production must meet customer standards. Therefore, employee performance determines the desired quality of work. Researchers will investigate the relationship between employee loyalty and organizational commitment by examining how employee engagement influences employee performance. The results of this study can provide input to management for future follow-up. Researchers used descriptive statistics using Smart PLS 4.0 to analyze data and identify factors related to employee loyalty and organizational commitment, which increase company productivity by mediating employee engagement to employee performance. Questionnaires were distributed to 158 employees using Google Forms. Engagement and performance are strongly and positively influenced by employee loyalty. While organizational dedication has a positive and significant effect on employee performance. What significantly mediates the relationship between employee loyalty, organizational commitment, and employee performance is employee engagement, which is strongly correlated with it. Employee loyalty and organisational commitment indirectly affect employee performance through employee engagement, suggesting that these factors may indirectly improve performance through employee engagement.